Genomic epidemiology demonstrates spatially clustered, local transmission of Plasmodium falciparum in forest-going populations in southern Lao PDR. - Ying-An Chen; Eric Neubauer Vickers; Andres Aranda-Diaz; Maxwell Murphy; Inna Gerlovina; Francois Rerolle; Emily Dantzer; Bouasy Hongvanthong; Hsiao-Han Chang; Andrew A Lover; Nicholas J Hathaway; Adam Bennett; et al. (PLoS Pathogens, 2024)
While there has been significant progress in controlling falciparum malaria in the Lao People's Democratic Republic (PDR), sporadic cases persist in southern provinces where the extent and patterns of transmission remain largely unknown. To assess parasite transmission in this area, 53 Plasmodium falciparum (Pf) positive cases detected through active test and treat campaigns from December 2017 to November 2018 were sequenced, targeting 204 highly polymorphic amplicons. Two R packages, MOIRE and Dcifer, were applied to assess the multiplicity of infections (MOI), effective MOI (eMOI), within-host parasite relatedness, and between-host parasite relatedness ([Formula: see text]). Genomic data were integrated with survey data to characterize the temporal and spatial structures of identified clusters. The positive cases were mainly captured during the focal test and treat campaign conducted in 2018, and in the Pathoomphone area, which had the highest test positivity and forest activity. About 30% of the cases were polyclonal infections, with over half of theses (63%) showing within-host relatedness greater than 0.6, suggesting that cotransmission rather than superinfection was primarily responsible for maintaining polyclonality. A large majority of cases (81%) were infected by parasites genetically linked to one or more other cases. We identified five genetically distinct clusters in forest fringe villages within the Pathoomphone district, characterized by a high degree of genetic relatedness between parasites (mean [Formula: see text] = 0.8). Four smaller clusters of 2-3 cases linked Moonlapamok and Pathoomphone districts, with an average [Formula: see text] of 0.6, suggesting cross-district transmission. Most of the clustered cases occurred within 20 km and 2 months of each other, consistent with focal transmission. Transmission clusters identified in this study confirm the role of ongoing focal parasite transmission occurring within the forest or forest-fringe in the highly mobile population.